2019
DOI: 10.1155/2019/1265175
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide-Induced Autophagy Inhibits Its Insulin Secretion-Improving Function in β Cells

Abstract: Diabetes is a metabolic disease, partly due to hypoinsulinism, which affects ∼8% of the world’s adult population. Glibenclamide is known to promote insulin secretion by targeting β cells. Autophagy as a self-protective mechanism of cells has been widely studied and has particular physiological effects in different tissues or cells. However, the interaction between autophagy and glibenclamide is unclear. In this study, we investigated the role of autophagy in glibenclamide-induced insulin secretion in pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…A recent study reported that pretreatment with rapamycin, an mTOR inhibitor, induces autophagy and significantly decreases the insulin content in NIT-1 cells ( 35 ). Another study reported similar results, indicating that the level of insulin significantly increases due to glibenclamide, and further increases with 3-MA ( 36 ). Collectively, these findings suggest that suppressing autophagy increases β-cell insulin secretion.…”
Section: Autophagy and T2dmmentioning
confidence: 63%
“…A recent study reported that pretreatment with rapamycin, an mTOR inhibitor, induces autophagy and significantly decreases the insulin content in NIT-1 cells ( 35 ). Another study reported similar results, indicating that the level of insulin significantly increases due to glibenclamide, and further increases with 3-MA ( 36 ). Collectively, these findings suggest that suppressing autophagy increases β-cell insulin secretion.…”
Section: Autophagy and T2dmmentioning
confidence: 63%
“…Autophagy is important for maintaining cellular homeostasis and is involved in the pathogenesis of a myriad of diseases, such as metabolic disorders, cancers, neurodegenerative diseases, and pathogen infections [ 114 117 ]. Interestingly, alteration in Golgi-associated Rab GTPase is also implicated in these diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It belongs to the sulfonylurea group and acts to increase insulin secretion by directly closing ATP-sensitive K channels in pancreatic cells, causing depolarization of the membrane, opening Ca 2 + voltage-dependent channels, and leading to intracellular Ca 2+ influx and elevation, triggering insulin exocytosis. 40 Bixa orellana has demonstrated hypoglycemic effects in healthy 41 and diabetic animal models. 42 However, its mechanism of action is still unclear.…”
Section: Discussionmentioning
confidence: 99%